Impact of The Implementation of PSAK 72 and Psak 73 on Financial Performance: Study Literature Review - Adellya Putri Rezanti; Ela Tri Arisma; Indah Dwi Astuti; Gita Nur Walida; Ardyan Firdausi Mustoffa (LPPM POLITEKNIK LP3I BANDUNG, 2023)
This study was conducted with the aim of analyzing the impact of the implementation of PSAK 72 and PSAK 73 on financial performance. This study uses the literature review method from search results related to the application of PSAK 72 and PSAK 73 to financial performance. The research data is in the form of secondary data obtained from electronic databases such as Publish or Perish 7 and using manual searches via Google Scholar. The population in this study were 21 articles with a sample of 12 articles taken by purposive sampling technique. Based on the results of the research, it shows that there is an impact of the implementation of PSAK 72 and PSAK 73 on the company's financial performance.